Proses Pelapisan Krom pada Material ABS (Acrylonitrile Butadiene Styrene) - Ikaningsih, Manty Aldilani (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
Plating on plastic (POP) is a technology to increase mechanical properties and aesthetic value of plastic materials, so that material is protected and more durable. In addition, metal-coated plastic will look more good and shiny. In this study, ABS material was coated with chrome through an electroplating proces. It is hoped that the chrome coated ABS will have a good resistant to abration, resistant to chemicals, and a good electrical conductivity. The stages of the process carried out in the process of chrome electroplating on ABS material are sanding – soak cleaning – etching – neutralization – catalization – acceleration – Ni electroless – Ni electroplating – Cr electroplating. Based on the experiments that have been carried out chrome layer coated ABS material properly and homogenous.